Transition to Accrual Accounting - Khan, Abdul (Technical Notes and Manuals; Technical Notes and Manuals, 2009)
This technical note and manual addresses the following main questions: 1. What is accrual accounting? 2. What are the reasons for moving from cash to accrual accounting? 3. What are the differences between accrual accounting and accrual budgeting? 4. What are the main steps to be taken in moving from cash to accrual accounting? 5. What are the preconditions for introducing accrual accounting? 6. How should a move to accrual accounting be sequenced and managed in relation to the government overall agenda for public management reform?